Improvement of risk management through an Emergency Plan in mining companies, 2021 - Marquina Vargas, Diego Patricio (2022)
The purpose of this study was to determine the relationship between the emergency plan and the improvement of risk management in mining companies. The methodology was of the applied type, quantitative approach, pre-experimental design, and propositional correlation level. The results obtained were that the identification of potential risks was improved by 69.23%; the inventories of the technical means of self-protection were improved by 109.09%, the training of the emergency committee by 50%, the evaluation of emergencies by 64.29%, the review and monitoring of the emergency plan by 71.43%, the risk control by 90.91% and the risk process by 84.62%. It is concluded that the emergency plan has a significant relationship with the improvement of 87.50% of the risk management (Duze & Reddy, 2020), (Frank et al., 2018) of the mining company, going from a compliance level rate of 48% to 90%.